SELECTING THE PLACE FOR INSTALLATION OF PRESSURE SENSORES FOR REGISTRATION OF OSCILLATORY PROCESSES OF FUEL - Bulgakov, M.; Zenkin, E.; Булгаков, М. П.; Зенкін, Є. Ю.; Булгаков, Н. П.; Зенкин, Е. Ю. (Харьковский национальный автомобильно-дорожный университет, 2016)
The article deals with the possibility of using various pressure control devices for diagno-sing the units of gasoline engine. Diagnosing is offered to be carried out using the fluctuations of fuel pressure oscillation in a fuel rail. Research on various fuel systems is conducted and is used in various modes of sensors connection.
ВИБІР МІСЦЯ РОЗТАШУВАННЯ ДАТЧИКІВ ДЛЯ РЕЄСТРАЦІЇ ПРОЦЕСІВ КОЛИВАННЯ ПАЛИВА
ВЫБОР МЕСТА РАСПОЛОЖЕНИЯ ДАТЧИКОВ ДЛЯ РЕГИСТРАЦИИ ПРОЦЕССОВ КОЛЕБАНИЯ ТОПЛИВА
Keywords: fuel; gasoline; oscillation process; rail; technique; sensor; injector; pressure dropping; diagnosis; oscillogram; датчик; форсунка; тиск; діагностування; осцилограма; датчик; форсунка; давление; диагностирование; осциллограмма; 621.436